2000
DOI: 10.4315/0362-028x-63.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Isolation of Campylobacter from Roasted Chicken Samples from Mexico City

Abstract: The presence of Campylobacter spp. was investigated in 100 samples of roasted chicken tacos sold in well-established commercial outlets and semisettled street stands in Mexico City. From 600 colonies displaying Campylobacter morphology only 123 isolates were positive. From these isolates, 51 (41%) were identified as C. jejuni, 23 (19%) as C. coli, and 49 (40%) as other species of this genus. All of the 27 positive samples came from one location where handling practices allowed cross-contamination of the cooked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…In our study, Campylobacter jejuni was found in only 1 (3.7%) of 27 samples from retail vendors and none from street vendors. This is slightly greater than the prevalence found in another study of roasted chicken from Mexico that reported no bacterial contamination (2) but less than the prevalence reported by Quiñones-Ramírez et al (27%), which was also a study of cooked chicken from Mexico (20). The sample that was positive for C. jejuni was also positive for E. coli.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, Campylobacter jejuni was found in only 1 (3.7%) of 27 samples from retail vendors and none from street vendors. This is slightly greater than the prevalence found in another study of roasted chicken from Mexico that reported no bacterial contamination (2) but less than the prevalence reported by Quiñones-Ramírez et al (27%), which was also a study of cooked chicken from Mexico (20). The sample that was positive for C. jejuni was also positive for E. coli.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, a Mexican study found that 27% of roasted chicken tacos from catering premises were contaminated with Campylobacter spp. (Quinones‐Ramirez et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The serotypes of the organisms isolated in Thailand were similar to those of organisms isolated from humans. In Mexico City, a survey of ready-to-eat roasted chickens showed that they were contaminated with campylobacters ( 74 ). In developed countries, risk factors associated with foods include occupational exposure to farm animals, consumption of raw milk or milk products, and unhygienic food preparation practices ( 2 ).…”
Section: Foodsmentioning
confidence: 99%